Long-term performance of stone-cutting tools. (March 2015) - Rosa, L.G.; Fernandes, J.C.; Anjinho, C.A.; Coelho, A.; Amaral, P.M.
Abstract: This research work addresses the long-term performance – up to 5 m 2 of area of cut – of diamond-impregnated segmented discs used for hard stone cutting. Comparative studies amongst "geometrically equal" tools were carried out through the assessment of their cutting behaviour, under real conditions, using the same type of stone (Porriño granite). Several types of plots are used to monitor the performance of the tool, e.g. graphs of resultant force (generated by the contact between the tool and the stone slab) versus area of cut; and graphs of tool wear (weight loss) versus area of cut. Six discs were studied. The performance of each disc was observed along the cutting operation involving a considerably high area of cut, e.g. 625 linear metres of cut using an average cutting depth of 8 mm (equivalent to 5 m 2 of area of cut). Different types of matrices were used for manufacturing new segments for the cutting discs (the diamond content in the segments was kept constant). Matrices containing: Co + bronze (50 wt.%Co + 50 wt.% of a 90Cu–10Sn bronze); Co + bronze + 2.5 wt.% graphite; Co + bronze + 5.0 wt.% graphite; Co + bronze + 10 wt.% WC; and Co + bronze + 20 wt.% WC, were produced and their behaviour was compared to that of a standard disc available in the market and commonly used by the stone industry for cutting granite. Interesting alterations in cutting regimes were observed during the long-term tests. The evolution of resultant force and tool wear rate as a function of the area of cut is analysed, revealing that an increase in the resultant force is associated to a decrease in the wear rate of the tool, and vice versa. Highlights: Long-term tests were conducted up to 5 m 2 of area of cut. Force, tool wear, and electrical energy consumption were monitored along the cutting operation. Tests allowed the detection of interesting changes in tool behaviour along the tool life. A new matrix containing cobalt + bronze + graphite was used for the first time.